Public participation in healthcare safety: A tripartite evolutionary game model with evidence from diverse international cases - Zhiqiang Zeng; Saratha Sathasivam; Jing Xin; Huan Zhao (PLoS ONE, 2026)
As healthcare systems grow in complexity, ensuring medical safety requires moving beyond traditional top-down regulation. While public participation is increasingly recognized as a vital component, a robust, generalizable framework to guide its implementation has been lacking. This study addresses this critical gap by proposing and rigorously validating a tripartite evolutionary game model that integrates the public, medical institutions, and government authorities. We test the model’s universality and effectiveness against empirical data from three diverse international case studies: tuberculosis (TB) treatment adherence in Saudi Arabia, COVID-19 vaccination compliance in China, and antibiotic prescription supervision in Vietnam. Our analysis reveals that higher health risks and public exposure rates act as powerful catalysts, significantly enhancing participation from both the public and institutions, thereby accelerating the system’s convergence to a stable, compliant state. We also find that medical institutions are highly sensitive to penalty intensity, adopting compliant practices only when a critical threshold is surpassed. These findings confirm the existence of a “virtuous cycle,” where engaged citizens and stringent oversight collaboratively improve medical compliance, a mechanism that holds true across varied healthcare contexts. This research provides not only a validated theoretical framework but also actionable insights for policymakers to design evidence-based, participatory regulatory strategies that can enhance the resilience and sustainability of global healthcare systems.